A recent review on advancements in dimensional accuracy in fused deposition modeling (FDM) 3D printing - Azhar Equbal; Ramesh Murmu; Veenit Kumar; Md. Asif Equbal (AIMS Materials Science)
Fused deposition modeling (FDM) fabricated components have gained significant attention and widespread adoption across modern industries due to their versatility, serving as both prototypes and final products. FDM offers rapid and cost-effective prototyping and production capabilities; however, utilizing directly manufactured FDM parts is not practical. Secondary operations like post-processing, testing, and validation are typically required to ensure that the fabricated parts meet the necessary standards for their intended applications. Desired repeatability, reproducibility, reliability, and preciseness should be the main prerequisites of the part fabricated. It is desirable that additive manufacturing (AM) products should be produced with advanced control processes which should possess acceptable quality characteristics. Ensuring the dimensional accuracy of FDM parts is very crucial, and hence it is important to emphasize the key factors that influence the dimensional precision during their fabrication. Sharing insights into these critical factors is essential to steer scholars, researchers, and the AM industry towards informed decisions and future advancements in AM. We aimed to outline the significant factors influencing the dimensional accuracy of the FDM part. These research papers are collected from Scopus and web of science data using 'FDM' and 'dimensional accuracy' as the keywords. We include the latest papers published especially during 2020 to 2024, which were lacking in earlier research.